2008
DOI: 10.1111/j.1440-1673.2008.02018.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thickness and appearance of anterior talofibular and calcaneofibular ligaments in normal versus abnormal ankles with MRI

Abstract: Injuries to the lateral ligaments of the ankle are common in medical practice. The most commonly injured ligaments are the anterior talofibular (ATFL) and calcaneofibular (CFL) ligaments. When undertaking MRI evaluation of ankle injuries it is important to understand the normal dimensions, appearance and variations of these ligaments. Twenty-eight consecutive patients referred for MRI of the ankle underwent bilateral scanning. The thickness of normal and abnormal ATFL and CFL was determined. The mean thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 22 publications
5
40
2
Order By: Relevance
“…An MRI based study by Dimmick et al [4] reported ATFL thickness to be twice (2.19 mm) that of the current study (1.01 mm), with Hua et al [10] reporting ATFL thickness in normal ankles (1.46 mm) being less than in injured ankles (2.71 mm). Determining ligament dimensions from MRI images will to some extent be influenced by image resolution and slice thickness, and as such are not directly comparable to direct measurement.…”
Section: Discussionmentioning
confidence: 38%
See 3 more Smart Citations
“…An MRI based study by Dimmick et al [4] reported ATFL thickness to be twice (2.19 mm) that of the current study (1.01 mm), with Hua et al [10] reporting ATFL thickness in normal ankles (1.46 mm) being less than in injured ankles (2.71 mm). Determining ligament dimensions from MRI images will to some extent be influenced by image resolution and slice thickness, and as such are not directly comparable to direct measurement.…”
Section: Discussionmentioning
confidence: 38%
“…The width was reported in a number of studies which was reported to be ranging between 4 mm and 12.98 mm [18,21,22,28,30]. Dimmick et al [4] and Hua et al [10] used MRI to measure ATFL thickness which was reported to be 2.19 mm and 1.46 mm respectively.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The CFL extends proximally from the fibular tip, deep to the peroneal tendons, distally to the posterolateral calcaneus, which show long course through the fat tissue (29). The CR was expectedly superior in VISTA than in VISTA SPAIR between fat and CFL, which is attributable to the "undisclosive" effect due to signal loss of CFL by suppression of intraligamen- (31). Poor traceability of CFL might also be due to the signal intensity of healed/inherently heterogeneous-natured CFL which is similar to the adjacent suppressed fat.…”
Section: Discussionmentioning
confidence: 99%